Les emprunts à l’anglais touchés par la réforme orthographique et leur variation dans la presse canadienne en ligne - Fabrycy, Małgorzata (Neophilologica, 2020)
This article examines if and how the recommendations of the spelling reform from 1990 are applied and used in practice. We have focused especially on the loanwords namely anglicisms in the Canadian French and their employment in the Canadian press in electronic format. For that purpose, we wanted to depict certain details of the spelling reform concerning words of foreign origin, and more precisely those which are borrowed from British and American English. We have also concentrated our attention on the difficulties of French grammatical system, comparing it with the Italian and Spanish grammatical systems in order to illustrate the level of complexity of the French language. To demonstrate and verify the usage of the rules recommended by the reform of French orthography, we have chosen several online versions of Canadian daily press.